The Importance of Planning the Development of Critical Thinking Skills in the Expected Learning Outcomes of Subject-Based Curricula - Sušić, Merjem (Društvene i humanističke studije (Online), 2024)
The aim of this article is to make a theoretical review of the requirement for the development of critical thinking as one of the most important skills today, known as the 4K skills of the 21st century. Critical thinking lies at the base of moral conduct and authentic intellectual growth, and as such is crucial to the prosperity of society as a whole. The complexity of critical thinking is reflected in the fact that it takes numerous cognitive processes to initiate it and the acquisition of a specific set of knowledge, skills and values that should conduct it. Critical thinking is a generative competence whose actuality transcends space and time, and due to the ubiquity of situations in which there is a need for it, it should not be neglected within the framework of school learning and teaching outcomes. The methodology for creating the expected learning outcomes in the curriculum approach is usually guided by Bloom’s taxonomy, but the hierarchy of this taxonomy is not compatible with the hierarchy of critical thinking skills, which is why, when defining the expected learning outcomes, it would be more adequate to use the table of critical thinking competencies proposed by Iva Buchberger. Finding the best available ways of practicing critical thinking skills in class is the duty of modern pedagogy, so that the school fulfills its obligation to form the personality of students who are capable of competent decision-making and action.